Community Perception on the Development of the Tourism Industry in Improving the Welfare of the Community in Mandalika KEK - Triana Lidona Aprilani; Fathurrahman (Kusuma Negara Business School, 2021)
Apart from the increasing progress of the tourism sector, good tourism management will benefit industry players who have an impact on overcoming unemployment and poverty. The purpose of this study is to find out how the public's perception of the development of the tourism industry in improving the welfare of the community in the Special Economic Zone (SEZ) Mandalika. The analytical technique used in this research is using convenience sampling technique which is rarely used in previous tourism research on Lombok Island in general. The results showed that the development of the tourism industry in improving the welfare of the people in the Mandalika SEZ got the highest perception and there was also the lowest perception of the average value of 281 sample respondents. The findings from this study, the perception of both the public and the private sector on the sustainability of the development of the tourism industry has a direct and insignificant effect on the welfare of the community. This shows that the existence of the Mandalika Special Economic Zone (SEZ) does not play a significant role in the welfare of the community. This means that both the community and the private sector in the development of the Mandalika Special Economic Zone (SEZ) can strengthen cooperation and have dual functions.